Humoral and cell-mediated immune responses in HIV-vertically infected young patients after three doses of the BNT162b2 mRNA SARS-CoV-2 vaccine - Vanetti, Claudia; Stracuzzi, Marta; Crivellaro, Elisa; Ciciliano, Federica; Garziano, Micaela; Fenizia, Claudio; Biasin, Mara; Rubinacci, Valeria; Amendola, Antonella; Tanzi, Elisabetta; Zuccotti, Gian Vincenzo; Clerici, Mario; et al. (Frontiers in Immunology, 2024)
Data on the efficacy of three SARS-CoV-2 mRNA BNT162b2 vaccine doses and the role of previous SARS-CoV-2-infection in enhancing vaccine immunogenicity in HIV-vertically-infected people living with HIV (PLWH) are limited, as is the duration of vaccine-induced responses.CoV-2 plasma neutralizing activity (NA) against the European (B.1), Delta (B.1.617.2) and Omicron (B.1.1.529) variants and cell-mediated immunity (CMI) were analyzed in 29 ART-treated young PLWH (mean age 27.9 years) and 30 healthy controls (HC) who received three BNT162b2 vaccine doses. Individuals were stratified based on the presence/absence of previous SARS-CoV-2 infection (infected and vaccinated -SIV-; uninfected and vaccinated -SV-). Analyses were performed before vaccination (T0), 25 days from the second dose (T1), the day the third dose was administered (T2), and 3 months after the third dose (T3).In PLWH: i) NA against all variants was higher in SIV compared to SV at T2 and was increased at T3; ii) switched-memory plasmablasts were augmented in SIV alone at T2 and T3; iii) a SARS-CoV-2 specific T cell memory was generated; iv) IFN-γ-secreting CD4+ and CD8+ T lymphocytes were boosted at T3 mainly in SV. CMI magnitude was reduced in PLWH compared to HC. Notably, after the third dose of vaccine viremia was unmodified, but CD4 T cell counts were reduced>20% in 3/29 PHLW.A third dose of BNT162b2 vaccine induces strong humoral and CMI responses in young ART-treated PLWH independently from a previous SARS-CoV-2 natural infection. The lower magnitude of CMI responses should be considered when planning mRNA vaccine booster doses in PLWH.